Towards developing the butterfly sequence - Mohd Darus, Maizon; Ibrahim, Haslinda; Karim, Sharmila (AIP Publishing LLC, 2019)
The initial idea of Half Butterfly Method (HBM) has been introduced in 2015 to solve the geometric representation of distinct Hamiltonian circuit with different path in Kn. Based on this HBM, this paper will further explore the concept of Butterfly sequence. The sequence is constructed by fixing a vertex and creating direction between the other vertices. The total directions of n will give the value of nth Butterfly sequence. This paper will illustrate the construction of Butterfly sequence (Bs) for 1 ≤ s ≤ 5. In addition to that, characteristics of the Butterfly sequence will be formulated towards developing the sequence.